Private sector development: Business plan or development strategy? - Karin Küblböck; Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2015)
Private sector development (PSD) has taken on an increasingly prominent role in international development cooperation. This note argues that the private sector has to play an important role in sustainable economic and inclusive development but points out three concerns for effective PSD interventions: PSD is not a 'technical solution' but there are different theoretical approaches to the question which policies support a sustainable and inclusive private sector. There is no 'one' homogenous private sector but important interest conflicts and the interest of foreign firms should not be equated with the interest of the local private sector and national development concerns. A pro-development international policy environment in particular in the areas of trade and investment policies is crucial for PSD which stresses the importance of donors' policy coherence.
Keywords: 330